FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT KEMBALI BEKERJA KE MALAYSIA PADA MASYARAKAT KECAMATAN BEDUAI - Akwila, Agavita; Syahrudin, Husni; Budiman, Jumardi (Universitas Tanjungpura, 2023)
This study aimed to observe the effect of age, marital status, employment status, education level and income on the intention to return to work in Malaysia in the Beduai sub-district community, Sanggau district (2018-2022 period). The applied research method is associative with a causal form. The data source in this study were former migrant workers from Malaysia who returned from 2018-2022 with a total sample of 67 respondents. The technique used is nonprobability sampling with census sampling method. The data analysis technique applied is multiple regression analysis, t test, F test, and the coefficient of determination (R2). The results of this study reveal that: The variables of employment status, education level and income variables have a significant effect on the intention to return to work, while the variables of age and marital status have no significant effect on the intention to return to work in Malaysia.